2000
DOI: 10.1111/j.1469-445x.2000.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Potassium Currents in the Rabbit Pulmonary Arterial Circulation

Abstract: The response of pulmonary arteries to hypoxia varies as a function of vessel diameter. Small intrapulmonary resistance arteries are thought to be the main site of hypoxic pulmonary vasoconstriction (HPV), with hypoxia causing minimal contraction or even dilatation in large, conduit vessels. This has been proposed to reflect a differential distribution of morphologically and electrophysiologically distinct pulmonary artery smooth muscle (PASM) cells. We investigated longitudinal heterogeneity in smooth muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
2
5
1
Order By: Relevance
“…2, the intensity of Kv1.5 immunostaining appeared to be modestly greater in resistance than in conduit pulmonary arteries. In contrast to Archer et al (3), we, like McCulloch et al (22), found no evidence of K ϩ channel heterogeneity within the vascular wall of either conduit or resistance vessels (Figs. 2 and 3).…”
Section: Immunoblot Analysis Of Kcontrasting
confidence: 99%
See 2 more Smart Citations
“…2, the intensity of Kv1.5 immunostaining appeared to be modestly greater in resistance than in conduit pulmonary arteries. In contrast to Archer et al (3), we, like McCulloch et al (22), found no evidence of K ϩ channel heterogeneity within the vascular wall of either conduit or resistance vessels (Figs. 2 and 3).…”
Section: Immunoblot Analysis Of Kcontrasting
confidence: 99%
“…2 and 3). This does not rule out heterogeneous expression of subunits that were not examined; however, our results support the more recent data of McCulloch et al (22).…”
Section: Immunoblot Analysis Of Ksupporting
confidence: 67%
See 1 more Smart Citation
“…The disparity between the pharmacology of I KV and the resting potential suggests that it is not the underlying K + current. Moreover, I KV density was comparable with PASMCs from other species, including rat (Manoury et al 2009), rabbit (McCulloch et al 2000), pig (Evans et al 1998) and human (Shimoda et al 2001 b ).…”
Section: Discussionmentioning
confidence: 52%
“…The predominant site of hypoxic pulmonary vasoconstriction (HPV) in the lung appears to be in the small pulmonary resistance arteries (< 200-300 μm diameter) (Shirai et al, 1986;Kato and Staub, 1996). These regional differences between conduit and resistance PASMCs may reflect distributional differences in Kv and BKCa channels (Archer et al, 1996McCulloch et al, 2000;Smirnov et al, 2002;. For example, conduit PASMCs predominantly express BKCa channels, which results in more sensitive inhibition by TEA or the specific BKCa channel blocker, charybdotoxin (Garcia et al, 1991).…”
Section: Regional Diversity Of Kv Channels In Pasmcsmentioning
confidence: 99%